Proposed Method for Efficient Block Cipher Cryptography - Alregabo, Amina Khaled Khalel; Ismail, Yassen Hikmat (Eximia, 2023)
After the use of the Internet and the transmission of files between users expanded, information security became one of the important priorities for securing information by different means and methods. The information encryption comes at the forefront of the techniques used in information security. Encryption has been known since ancient ages. So, traditional methods appeared that quickly and greatly developed. They are still used in many scientific studies and developmental research with the aim of developing new methods for encryption of substitutions and increasing its ability to confront various attacks. The traditional methods were subjected to several attacks that they prompted researchers to develop them and overcome their weaknesses in front of those attacks. Some combinations of these methods are used to design new encryption methods based on overlapping ideas of traditional encryption. This paper sought to use a set of traditional encryption methods in designing a new system. In which, these methods are mixed with modern ideas that help increase the strength of encryption and its ability to face potential attacks. Caesar, Vigenère, Rail Fence, and transpose ciphers, with the idea of cipher cycles and segments and division into two parts in block ciphers. The proposed system relied on the chaotic function Tent map for its random properties in generating a string of keys consisting of 112 random characters in length using Python 3.11 programming language. The text was cut into Blocks of 108 characters. Each Block was divided into two parts. A part of the key was added to each section. A rial fence method was applied. Then Vigenère method with the key is applied. The proposed system processed the original text within the framework of the encryption cycles with the use of substitution in the order of the columns, shifting to the right, and the replacement of the sequence of the elements of each side according to the order of the elements of the other side. After the end of the encrypting cycles, the cipher block is added to the final ciphertext. The operations were repeated for the next block until the last block is finished. For the purpose of decrypting, the previous operations are repeated in reverse order to obtain the original text, by decrypting blocks of the cipher text. The proposed system achieved extreme accuracy in extracting the original text. The system was evaluated by measuring the time and throughput of the encryption and decryption. The encryption and decryption times were short for short texts, which increased with the increase in the length of the text, with a relatively stable encryption and decryption throughput. The system achieved acceptable memory consumption in short texts but increased by the length of the text size. The achieved Avalanche test was less than (50%).